Integrating total quality management in religious education programs: a case study of Ramadan academy for outcome-based accreditation - Sarbini, Sarbini; Suhendi, Saca; Suhartini, Andewi; Muttaqin, Via Putrimawati; Maulana, Hamdan; Koswara, Ujang; Hambali, Wisnu; Suganda, Ayub (Jurnal Pendidikan Agama Islam Al-Thariqah, 2026)
Educational accreditation in the post-pandemic era has shifted toward Outcome-Based Accreditation, yet many Islamic institutions remain trapped in administrative formalities that fail to measure substantive character growth. While recent literature (2021-2024) emphasizes digital quality assurance, a critical research gap persists: there is a lack of empirical models showing how Total Quality Management can be synthesized with traditional pesantren-based curricula to meet the rigorous Graduate Competence Standards mandated by terbaru regulations like Permendikbudristek No. 28 of 2021. This study analyzes the "Ramadan Academy" at SMA Plus Yaspida Sukabumi, evaluating its role as a strategic catalyst for "Superior Accreditation". Beyond mere procedural description, this research scrutinizes the structural convergence between the PDCA cycle and spiritual habituation. The novelty lies in the transformation of religious activities—muhadhoroh and tadarus—into a measurable "character laboratory" that generates high-fidelity data for stakeholder satisfaction and output effectiveness. However, a limitation is noted in the institutional-specific nature of the integration, which requires strong instructional leadership to synchronize school and pesantren schedules. This analysis concludes that TQM does not secularize religious education but rather provides the meticulousness (itqan) necessary to validate spiritual outcomes within a globalized, data-driven accreditation landscape.